Corneal Confocal Microscopy Identifies Structural Small Fibre Abnormalities in an Adolescent with Type 1 Diabetes and Impaired Awareness of Hypoglycaemia - Banerjee, Mainak; Mukhopadhyay, Pradip; Basu, Madhurima; Ghosh, Sujoy (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Impaired awareness of hypoglycaemia (IAH) is present in around 25-40% of individuals with type 1 diabetes mellitus (T1DM). Herein, we present a case of an adolescent with T1DM and IAH who had worse corneal nerve parameters compared to a T1DM adolescent without IAH. Small fibre abnormalities detected by corneal confocal microscopy in an objective easy-to-perform non-invasive test might be a surrogate indicator of underlying autonomic dysfunction in T1DM and IAH.